Analysis of Physical and Chemical Properties of Eucalyptus Oil in Suli Vilage, Salahutu Sub–District, Central Maluku District - Alfares E Elly; Lieke Tan; Herman Siruru (Jurnal Agrosilvopasture-Tech, 2023)
The purpose of this study was to determine the effect of leaf weight and storage time of eucalyptus leaves on yield, seniol content, specific gravity, refractive index, and optical rotation. This study used a factorial randomized block design with 2 factors, namely: treatment A (leaf weight) with 3 levels of treatment, namely: A1 = 3000 g A2 = 4000 g A3 = 5000 g, and factor B (storage time) with 3 levels of treatment B1 = 2 days of storage B2 = 4 days of storage B3 = 6 days of storage. Based on the results of the study, the yield of eucalyptus oil ranged from 0.44% - 0.94%, and the cineol content of eucalyptus oil was 46.7%-52.7%. The specific gravity of eucalyptus oil is 0.91%–0.93%. The optimal rotation of eucalyptus oil ranged from -2.16 to -3.94. Based on the Indonesian National Standard SNI 06-3954-2001, the physicochemical properties of eucalyptus oil, namely cineol content, specific gravity, refractive index, optical rotation, and solubility in ethanol 80% have values that meet SNI 06-3954-2001.